The XVIII, XIX, XX Centuries of Islamic Economic Thinking and Their Relevance in the Development of Contemporary Islamic Economy - Muhammad Sauqi (Budapest International Research and Critics University, 2022)
This study aims to determine the relevance of the Islamic economic thought of Banjar Ulama in the XVIII, XIX, and XX centuries with the development of contemporary Islamic economics. This type of research is descriptive qualitative library research with historical, sociological, anthropological, and legal approaches. The findings from this research are first, in general, Banjar Ulama of the XVIII and XIX centuries AD made books based on the social conditions of the people and because economic problems were regulated by the Banjar kingdom. Second, Banjar clerics made fiqh books on orders from other people. However, in the twentieth century AD, Islamic economic thought began to emerge because first, on the basis of a request from the Banjar community about the rule of Islamic economic law. Second, at that time Banjar Ulama saw a lot of fraud in economic transactions. The current development of Islamic economics cannot be separated from the history of Muslim thought about economics in the past. The involvement of Muslim thinkers in complex community life and the absence of separation of scientific disciplines make Muslim thinkers see community problems in a more integrative context.